Thinking like a slag heap: Environmental mobilization around the (post)extractivist territory of the Martinet in Charleroi - Grulois, Geoffrey; Moritz, Benoit; Declève, Marine (Journal of Delta Urbanism, 2026)
Based on fieldworks, interviews and mapping, this paper recounts the history of the Martinet site in Charleroi, Belgium. Located at the center of the fossil crescent, the Martinet was part of the dense network of collieries in the Caroloregian agglomeration and saw the emergence of environmental mobilization against extractivism at the end of the 1970s. The paper argues that the socio-environmental history of the Martinet reveals the ontological opposition between the extractivist logic of mining operations and the emerging practice of caring for the living soil initiated by local citizens from the 1970s. It unfolds the hypothesis that this environmental stewardship enacted by citizens and activists materializes the emergence of Aldo Leopold’s "land ethic" through which human reintegrate the biotic community of the living soil. While the history of environmental struggles against extractivism has brought to light many cases in South America and the global south, the story of the Martinet allows to delve deeper in the socio-environmental history of the fossil crescent. It also questions the future of Charleroi postextractivist territory, torn between the desire to revive industrial development and economic growth, and the attempt to enact a long-lasting relational ontology with the living soil.